Dos porões ao hospício : a participação das Santas Casas de Misericórdia na assistência aos alienados em Minas Gerais, no século XIX - Aline Moreira Gonçalves (2013)
In this dissertation, we seek to investigate the role of the Holy Houses of Mercy in assisting alienated people in Minas Gerais during the nineteenth century. For this purpose, we conducted a survey of Holy Houses of Mercy existing in the region of Minas Gerais/ Brazil, specifically across the Royal Road (Estrada Real). The relevance of this research lies mainly in the lack of information about the contribution of the Holy Houses of Mercy in the historical constitution process of assistance to alienated people in Minas Gerais throughout the nineteenth century. The Holy Houses of Mercy existing in Brazil and in Minas Gerais have played an active role since the colonial period by sheltering individuals with health problems or victims of social abuse. The specific objectives of this dissertation were: 1) conduct a systematic survey on the history of the Holy Houses of Mercy existing in Minas Gerais, located in the Royal Road, as well as the period of operation of these institutions; 2) identify the possibility of access to documentation about the therapeutics (knowledge and practice) associated with assisting alienated people in the period studied; 3) investigate the role played by Mercy in the actions of State over society, with regard to assisting alienated people and, thereby, contribute to the discussion of the relevance of religious institutions in assisting alienated people in Minas Gerais. The results lead us to conclude that there were 24 Holy Houses of Mercy in Minas Gerais built until the end of the nineteenth century. We also concluded that these Holy Houses emerged from the design of the Royal Road. Nevertheless, only the Holy Houses located in São João del Rei and Diamantina have provided systematic attention to alienated people during the nineteenth century in Minas Gerais. The Holy House of Diamantina even created the Hospice of Diamantina, which had a short existence, from 1889 to 1906. The role played by "Mercy" in the sheltering process of alienated people in Minas Gerais occurred in a very specific way. It was present not only through the presence of the Sisters of Charity and their practices, but also through the practice of lay people with the premise of Christian charity. We realized also that it was through religious legacy, many times private, that public policies regarding mental health care have developed, in the period of Brazil Republic.